Priestley’s Essay on a Course of Liberal Education (1764) and Jovellanos’s Memoria sobre la Educación Pública (1802): A comparative approach - Sell Maestro, Alejandro (Historia y Memoria de la Educación, 2019)
The Enlightenment was a multidisciplinary movement which deposited its hopes in education as a means to enable society to advance in, or at least maintain, its progress. However, not all figures of the Enlightenment viewed education in the same way since each was the product of their own vital circumstances and training. This is the case of Joseph Priestley and Gaspar Melchor de Jovellanos, who, though quite different in some respects, were similar in others. Born into a family of artisans in rural England and brought up in the strictest nonconformist tradition Priestley is, to all appearances, the complete opposite of Jovellanos, who belonged to the Asturian aristocracy and was raised in the tradition of Roman Catholic scholasticism. Yet, as this article aims to show, both were children of the Enlightenment who imbibed and disseminated its ideas; and both were writers with a broad range of interests who retained close links with their respective religious confessions and ended up being persecuted on account of their zeal for social reform. In consequence, their views on education, heavily influenced by their religious convictions, were at the same time very similar, above all in their opposition to the current scholastic systems, and yet different in sometimes surprising ways.